Prostate cancer mortality outcomes and patterns of primary treatment for Aboriginal men in New South Wales, Australia. (April 2015) - Rodger, Jennifer C.; Supramaniam, Rajah; Gibberd, Alison J.; Smith, David P.; Armstrong, Bruce K.; Dillon, Anthony; O'Connell, Dianne L.
Abstract : Objective: To compare prostate cancer mortality for Aboriginal and non‐Aboriginal men and to describe prostate cancer treatments received by Aboriginal men. Patients and methods: We analysed cancer registry records for all men diagnosed with prostate cancer in New South Wales (NSW) in 2001–2007 linked to hospital inpatient episodes and deaths. More detailed information on androgen‐deprivation therapy and radiotherapy was obtained from medical records for 87 NSW Aboriginal men diagnosed in 2000–2011. The main outcomes were primary treatment for, and death from, prostate cancer. Analysis included Cox proportional hazards regression and logistic regression. Results: There were 259 Aboriginal men among 35 214 prostate cancer cases diagnosed in 2001–2007. Age and spread of disease at diagnosis were similar for Aboriginal and non‐Aboriginal men. Prostate cancer mortality 5 years after diagnosis was higher for Aboriginal men (17.5%, 95% confidence interval (CI) 12.4–23.3) than non‐Aboriginal men (11.4%, 95% CI 11.0–11.8). Aboriginal men were 49% more likely to die from prostate cancer (hazard ratio 1.49, 95% CI 1.07–1.99) after adjusting for differences in demographic factors, stage at diagnosis, health access and comorbidities. Aboriginal men were less likely to have a prostatectomy for localised or regional cancer than non‐Aboriginal men (adjusted odds ratio 0.60, 95% CI 0.40–0.91). Of 87 Aboriginal men with full staging and treatment information, 60% were diagnosed with localised disease. Of these, 38% had a prostatectomy (± radiotherapy), 29% had radiotherapy only and 33% had neither. Conclusion: More research is required to explain differences in treatment and mortality for Aboriginal men with prostate cancer compared with non‐Aboriginal men. In the meantime, ongoing monitoring and efforts are needed to ensure Aboriginal men have equitable access to best care.